2021
DOI: 10.1186/s12906-021-03231-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in chemical composition and antimalarial activities of two samples of Terminalia albida collected from separate sites in Guinea

Abstract: Background The disparity of harvesting locations can influence the chemical composition of a plant species, which could affect its quality and bioactivity. Terminalia albida is widely used in traditional Guinean medicine whose activity against malaria has been validated in vitro and in murine models. The present work investigated the antimalarial properties and chemical composition of two samples of T. albida collected from different locations in Guinea. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Both BITC and the reference drug CQ displayed sigmoidal dose-response curves compatible with biological activity (Figure 1). The IC50 values and the resistance index calculated for CQ were consistent with previous results in similar laboratory conditions [32][33][34], hence validating the assay conditions. The resistance index provides a quantitative measure of activity against a resistant strain in comparison to a susceptible strain (RI=IC50 Dd2/IC50 3D7-GFP) [35,36].…”
Section: Dose-response Evaluationsupporting
confidence: 89%
“…Both BITC and the reference drug CQ displayed sigmoidal dose-response curves compatible with biological activity (Figure 1). The IC50 values and the resistance index calculated for CQ were consistent with previous results in similar laboratory conditions [32][33][34], hence validating the assay conditions. The resistance index provides a quantitative measure of activity against a resistant strain in comparison to a susceptible strain (RI=IC50 Dd2/IC50 3D7-GFP) [35,36].…”
Section: Dose-response Evaluationsupporting
confidence: 89%
“…Both BITC and the reference drug CQ displayed sigmoidal dose-response curves compatible with biological activity (Figure 1). The IC50 values and the resistance index calculated for CQ were consistent with previous results in similar laboratory conditions [38][39][40], hence validating the assay conditions. The resistance index provides a quantitative measure of activity against a resistant strain in comparison to a susceptible strain (RI = IC50 Dd2/IC50 3D7 − GFP) [41,42].…”
Section: Dose-response Evaluationsupporting
confidence: 89%
“…The chemical composition of a plant species can be influenced by the location of harvesting, which can affect its quality and bioactivity (Camara et al, 2021). Additionally, Tian et al (2016) have shown substantial variation in phytochemical components and the bioactivity of same species from various origins.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolite content is heavily influenced by genetic and environmental factors, though the extent of variation caused by these factors varies depending on the type of metabolite. Medicinal plants produce a large number of metabolites with diverse structures, all of which play important roles in plant growth, development, and environmental response (Camara et al, 2021). The study by Zhang et al (2017) have shown the connection between the effectiveness, chemical components, and distribution of the antimalarial medicinal plant, Artemisia annua L. collected from several geographic areas.…”
Section: Resultsmentioning
confidence: 99%